INTERVENSI TERHADAP ANAK USIA DINI YANG MENGALAMI GANGGUAN ADHD MELALUI PENDEKATAN KOGNITIF - Fitri Ani (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2022)
ADHD is a neurodevelopmental disorder in which a child presents a significant problem due to a lack of attention or hyperactivity-impulsivity. ADHD can interfere with the development of children in terms of cognitive, behavioral, socialization and communication. A common mistake that ADHD treatment through pharmacological therapy will eliminate all the symptoms of hyperactivity and impulsive problems in children with ADHD, but the use of ADHD drugs in the long term then it will affect the children. Another alternative for dealing with ADHD children using a counseling approach is behavioral cognitive behavioral approach and Adlerian play therapy.Understanding of behavioral cognitive approaches and Adlerian play therapy can help address early childhood problems especially those with ADHD disorders.